2004
DOI: 10.1080/10550490490265280
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacotherapy for Marijuana Dependence: A Double‐blind, Placebo‐controlled Pilot Study of Divalproex Sodium

Abstract: There is a noticeable lack of targeted treatment options for marijuana dependence, in particular pharmacologic approaches. This is the first study evaluating a targeted pharmacologic approach for marijuana dependence. The goals of the study were to determine if such patients would seek pharmacologic treatment, whether these patients could be retained in treatment using a design previously developed for cocaine-dependent patients, and especially whether divalproex sodium showed promise as a treatment agent for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
84
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(89 citation statements)
references
References 31 publications
(33 reference statements)
4
84
0
1
Order By: Relevance
“…In fact, divalproex did decrease marijuana craving during abstinence. However, the increased irritability, sleepiness, anxiety, and decreased social interaction during divalproex maintenance is consistent with the poor compliance and negative results obtained in a pilot clinical trial with divalproex (Levin et al, 2003). The impaired cognitive task performance is particularly problematic for a potential treatment medication, as this effect occurred throughout the entire divalproex maintenance period.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…In fact, divalproex did decrease marijuana craving during abstinence. However, the increased irritability, sleepiness, anxiety, and decreased social interaction during divalproex maintenance is consistent with the poor compliance and negative results obtained in a pilot clinical trial with divalproex (Levin et al, 2003). The impaired cognitive task performance is particularly problematic for a potential treatment medication, as this effect occurred throughout the entire divalproex maintenance period.…”
Section: Discussionmentioning
confidence: 54%
“…Compliance was also assessed quantitatively by plasma assays. The divalproex dose was chosen based on its use in previous studies as a mood stabilizer (eg Levin et al, 2003;Donovan et al, 2000;Giakas et al, 1990). Divalproex dosing started at 500 mg/day, which was increased every 2 days until a final maintenance dose (1500 mg/day) was achieved on the 9th day of administration.…”
Section: Pharmacotherapy Of Marijuana Withdrawal M Haney Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…Maintenance on two medications, the antidepressant, bupropion (Haney et al, 2001), and the mood stabilizer, divalproex (Haney et al, 2004), significantly worsened mood during marijuana withdrawal compared to placebo, suggesting that they would not show promise as treatment approaches. Similarly, a clinical pilot trial observed poor compliance and outcome using divalproex to treat marijuana dependence (Levin et al, 2004). The antidepressant, nefazodone, which is sedating compared to the stimulant-like bupropion, decreased a subset of marijuana withdrawal symptoms (Haney et al, 2003), but the medication that most effectively attenuated marijuana withdrawal was THC (dronabinol, Marinol).…”
mentioning
confidence: 99%
“…Thus far, clinical trials using psychotropic agents such as valproic acid and buspirone have been conducted with mixed results and no pharmacological intervention has demonstrated efficacy in reducing marijuana use (Levin et al, 2004;McRae et al, 2006). Human laboratory trials of the antidepressants nefazodone and bupropion for amelioration of marijuana withdrawal found nefazodone to be partially effective for control of marijuana withdrawal related anxiety and muscle pain while bupropion was ineffective, and aggravated marijuana withdrawal related mood symptoms (Haney et al, 2003;Haney et al, 2001).…”
mentioning
confidence: 99%